Philippines Economic Update, December 2021 : Regaining Lost Ground, Revitalizing the Filipino Workforce - World Bank (World Bank, Washington, DC, 2022)
The economic rebound gained momentum in the third quarter of 2021 despite another COVID-19 wave. The Philippines has, so far, faced its worst infection wave in September when the 7-day daily average reached about 21,000 cases due to the Delta variant. In response, the authorities reimposed stringent mobility restrictions in Metro Manila and other key metropolitan areas. Nonetheless, compared with previous waves, domestic activity has been less sensitive to infections. Public containment measures constrained overall mobility less, while households and firms have learned to cope with infections and diminished mobility. As a result, the growth momentum was not severely hampered, and the third quarter growth surprised on the upside, exceeding market expectations. The economy expanded by 4.9 percent in the first three quarters of 2021, rebounding from a 10.1 percent contraction over the same period in 2020. Although partially driven by base effects, the growth expansion also reflected an increase in economic activity despite the implementation of several lockdowns. Growth was supported by the industry sector, driven by double-digit growth in manufacturing and robust public construction activity. The services sector posted a more moderate expansion as some key services were subdued by mobility restriction measures. The agriculture sector contracted as farm and livestock outputs were impacted by typhoons and ongoing outbreak of African Swine Fever. Meanwhile, domestic demand improved, supported by a resurgence in public construction spending. Private consumption picked up but still tempered by elevated inflation and unemployment, mobility restrictions, and low consumer confidence. Public consumption growth eased, in part due to the base effects from the swift disbursement of fiscal support a year ago. The global economic recovery strengthened exports, although services trade remained weak. The fiscal stance remains supportive of economic recovery, but the policy space is narrowing. Public spending accelerated from 23.6 percent of GDP in the first three quarters of 2020 to 24.6 percent of GDP in the same period in 2021, in line with the recovery in public investment and ongoing fiscal support. Infrastructure outlays increased from 3.5 percent of GDP to 4.7 percent of GDP in the first three quarters of 2021, a result of the government’s push on investment spending as part of its recovery program. Meanwhile, public revenues fell from 16.8 percent of GDP in the first three quarters of 2020 to 16.3 percent of GDP over the same period in 2021. Tax revenues rebounded due to strong tax and customs collections, but non-tax revenue contracted following the significant dividend remittances to the Bureau of the Treasury (BTr) in the beginning of the pandemic. The fiscal deficit widened from 6.9 percent of GDP in Q1-Q3 2020 to 8.3 percent of GDP in Q1-Q3 2021. The wider fiscal deficit has resulted in higher financing needs, which have been met by increased public borrowing. Public debt increased from 54.6 percent of GDP at end-2020 to 63.1 percent of GDP at end-September 2021.